Imeglimin may affect hemoglobin A1c accuracy via prolongation of erythrocyte lifespan in patients with type 2 diabetes mellitus: insights from the INFINITY clinical trial - Osonoi, Takeshi; Shirabe, Shinichiro; Saito, Miyoko; Hosoya, Mitsuru; Watahiki, Norie; Shiozawa, Nana; Douguchi, Satako; Ofuchi, Kensuke; Katoh, Makoto (Frontiers in Endocrinology, 2025)
BackgroundImeglimin is a novel type 2 diabetes (T2D) drug that is expected to improve mitochondrial function. In phase 3 trials, imeglimin demonstrated a gradual reduction in hemoglobin A1c (HbA1c), with a plateau at approximately 20–24 weeks. As erythrocyte lifespan may affect HbA1c accuracy, this clinical trial aimed to evaluate the potential discordance between HbA1c and other glycemic markers following imeglimin therapy and to explore whether imeglimin affects erythrocytes.MethodsThis was a prospective, single-arm, open-label exploratory clinical trial (INFINITY study) conducted at Naka Kinen Clinic, Japan. Twenty-nine Japanese patients with inadequately controlled T2D received imeglimin 2,000 mg/day for six months. The primary endpoint was the change in hemoglobin concentration from baseline to Month 6. Secondary endpoints included serial changes in HbA1c, glycoalbumin (GA), 1,5-anhydroglucitol (1,5-AG), and erythrocyte lifespan, as well as comparison of glycemic reduction rates across these markers.ResultsThe change in hemoglobin concentration at 6 months was not statistically significant (mean ± SD: −0.2 ± 0.9 g/dL; p = 0.23). While HbA1c and GA decreased and 1,5-AG increased one month after imeglimin initiation, GA and 1,5-AG showed rapid changes compared to the gradual decrease in HbA1c. The divergence in reduction rates between HbA1c and the other markers persisted for up to two months. When erythrocyte lifespan was assessed using 3-month interval averages, significant prolongation was observed in both the 1–3 month and 4–6 month periods compared to the pre-treatment period (−2 to 0 months).ConclusionThis exploratory clinical trial suggests that imeglimin may prolong erythrocyte lifespan, resulting in disproportionately elevated HbA1c levels relative to true glycemic status. Reliance on HbA1c alone may underestimate imeglimin’s early glycemic effects, highlighting the value of alternative markers such as GA and 1,5-AG.Clinical trial registrationhttps://jrct.mhlw.go.jp/latest-detail/jRCTs031220489, Identifier jRCTs031220489.